Turning Forecasts into Actions: Marine Heatwaves and Ecosystem-Wide Impacts in Australian Waters During Summer 2024/25 - Alistair Hobday; Claire Spillman; Jason Hartog; Grant Smith; Jamie Allnutt; Fred Bailleul; Laura Blamey; Stephanie Brodie; Curtis Champion; Arani Chandrapavan; Melinda Coleman; Mark Doubell; et al. (Oceanography, 2026)
Widespread marine heatwaves (MHWs) affected Australia over the 2024/25 summer and autumn. They impacted marine species, ecosystems, and coastal communities, with emerging economic consequences. Across northern Australia, severe coral bleaching occurred for the first time along both the western and eastern coasts, and a mass fish kill occurred in Western Australia. In South Australia, prolonged MHW conditions and impacts from an extensive harmful algal bloom of the dinoflagellate Karenia included extensive fish kills, human health effects, losses for ocean-dependent industries, and currently unquantified effects on the broader marine ecosystem. In Tasmania, a range of impacts were linked to warm water, including blooms of salps, Noctiluca, and jellyfish. In New South Wales, a fish mortality event linked to thermal shock generated considerable community concern and media coverage. Trial seasonal forecasts available several months ahead of MHW emergence, combined with national marine climate briefings, helped prepare industry, researchers, and governments for possible impacts. This resulted in increased awareness and development of regional and industry MHW response plans with proactive strategies at both short and long timescales.

Co-creating water knowledge: a community perspective - Giulio Castelli; Ben C. Howard; Tanveer M. Adyel; Amir AghaKouchak; Afnan Agramont; Hafzullah Aksoy; Rossella Alba; Pedro H.L. Alencar; Amobichukwu C. Amanambu; Hasnat Aslam; Luna Bharati; Liduin Bos-Burgering; et al. (Hydrological Sciences Journal, 2025)

Use of alternatives to animal testing for Environmental Safety Assessment (ESA): Report from the 2023 EPAA partners’ forum - Jose V. Tarazona; Ana Fernandez-Agudo; Ondrej Adamovsky; Marta Baccaro; Natalie Burden; Bruno Campos; Björn Hidding; Karen Jenner; David John; Katia Lacasse; Adam Lillicrap; Delina Lyon; et al. (Regulatory Toxicology and Pharmacology, 2025)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Evaluation of the EMA log kow trigger for fish BCF testing based on data for several human pharmaceuticals - Lisa A. Constantine; Natalie Burden; Todd Davidson; David G. Dolan; Gemma Janer; Andreas Häner; Michael R. Lee; Samuel K. Maynard; Erick Nfon; Alison Nimrod Perkins; James J. Ryan; Joan Tell (Regulatory Toxicology and Pharmacology, 2024)

Taking the bait: Environmental factors affecting bait retention and hook disposition in the Gulf of Maine Bottom Longline Survey - Lindsey Noel Nelson; W. David McElroy; Andrew W. Jones; George A. Maynard; Chris Tholke; Anna J.M. Mercer (Fisheries Research, 2024)

Forecasting a Summer of Extremes: Building Stakeholder Response Capacity to Marine Heatwaves - Alistair Hobday; Claire Spillman; Jamie Allnutt; Melinda Coleman; Fred Bailleul; Laura Blamey; Stephanie Brodie; Arani Chandrapavan; Jason Hartog; David Maynard; Craig Mundy; Eva Plaganyi; et al. (Oceanography, 2024)
Forecasts of an El Niño in 2023/2024 raised concern among Australian marine stakeholders regarding its potential impacts on marine industries and systems. National level seafood-focused climate briefings were requested by the fisheries sector for the first time, driven by various state and regional level meetings and information requests. To respond to stakeholder needs, six virtual national marine climate briefings were undertaken through the austral 2023/2024 summer, underpinned by new subseasonal to seasonal marine heatwave forecast capabilities. These briefings were developed in collaboration with multiple science organizations and were targeted to industry and management authorities across the Australian seafood sector. As a result, targeted information products, additional regional and sector-specific briefings, and state response plans were developed. Collectively, these briefings were a catalyst for positive and rapid action in policy, management, industry, and research arenas. This experience showed that the combination of seasonal forecasting capability, inter-agency coordination, strong stakeholder engagement, and effective science communication plays a critical role in improving the understanding of, planning for, and responses to extreme events.

A network approach to analyse Australia’s blue economy policy and legislative arrangements - Miguel Frohlich; Pedro Fidelman; Ian Dutton; Marcus Haward; Brian W. Head; Dianne Maynard; David Rissik; Joanna Vince (Marine Policy, 2023)

Isometric-based test improves EMG-threshold determination in boys vs. men - Stacey Woods; Raffy Dotan; Nicole Jenicek; James Maynard; David Gabriel; Craig Tokuno; Bareket Falk (European Journal of Applied Physiology, 2019)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

(De)synchronization of advanced visual information and ball flight characteristics constrains emergent information–movement couplings during one-handed catching - J. A. Stone; I. W. Maynard; J. S. North; D. Panchuk; K. Davids (Experimental Brain Research, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Genetic structure of populations of whale sharks among ocean basins and evidence for their historic rise and recent decline - Thomas M. Vignaud; Jeffrey A. Maynard; Raphael Leblois; Mark G. Meekan; Ricardo Vázquez‐Juárez; Dení Ramírez‐Macías; Simon J. Pierce; David Rowat; Michael L. Berumen; Champak Beeravolu; Sandra Baksay; Serge Planes (Molecular Ecology, 2014)
This study presents genetic evidence that whale sharks, Rhincodon typus , are comprised of at least two populations that rarely mix and is the first to document a population expansion. Relatively high genetic structure is found when comparing sharks from the Gulf of Mexico with sharks from the Indo‐Pacific. If mixing occurs between the Indian and Atlantic Oceans, it is not sufficient to counter genetic drift. This suggests whale sharks are not all part of a single global metapopulation. The significant population expansion we found was indicated by both microsatellite and mitochondrial DNA . The expansion may have happened during the Holocene, when tropical species could expand their range due to sea‐level rise, eliminating dispersal barriers and increasing plankton productivity. However, the historic trend of population increase may have reversed recently. Declines in genetic diversity are found for 6 consecutive years at Ningaloo Reef in Australia. The declines in genetic diversity being seen now in Australia may be due to commercial‐scale harvesting of whale sharks and collision with boats in past decades in other countries in the Indo‐Pacific. The study findings have implications for models of population connectivity for whale sharks and advocate for continued focus on effective protection of the world's largest fish at multiple spatial scales.

The Development of an Ecosystem Services Framework for South East Queensland - Simone Maynard; David James; Andrew Davidson (Environmental Management, 2010)

Genome mosaicism is conserved but not unique in Pseudomonas aeruginosa isolates from the airways of young children with cystic fibrosis - Robert K. Ernst; David A. D′Argenio; Jeffrey K. Ichikawa; M. Gita Bangera; Sara Selgrade; Jane L. Burns; Peter Hiatt; Karen McCoy; Mitchell Brittnacher; Arnold Kas; David H. Spencer; Maynard V. Olson; et al. (Environmental Microbiology, 2003)
Summary Pseudomonas aeruginosa strains from the chronic lung infections of cystic fibrosis (CF) patients are phenotypically and genotypically diverse. Using strain PAO1 whole genome DNA microarrays, we assessed the genomic variation in P. aeruginosa strains isolated from young children with CF (6 months to 8 years of age) as well as from the environment. Eighty‐nine to 97% of the PAO1 open reading frames were detected in 20 strains by microarray analysis, while subsets of 38 gene islands were absent or divergent. No specific pattern of genome mosaicism defined strains associated with CF. Many mosaic regions were distinguished by their low G + C content; their inclusion of phage related or pyocin genes; or by their linkage to a vgr gene or a tRNA gene. Microarray and phenotypic analysis of sequential isolates from individual patients revealed two deletions of greater than 100 kbp formed during evolution in the lung. The gene loss in these sequential isolates raises the possibility that acquisition of pyomelanin production and loss of pyoverdin uptake each may be of adaptive significance. Further characterization of P. aeruginosa diversity within the airways of individual CF patients may reveal common adaptations, perhaps mediated by gene loss, that suggest new opportunities for therapy.

Novel Antifeedant and Insecticidal Compounds from Avocado Idioblast Cell Oil - Cesar Rodriguez-Saona; Jocelyn G. Millar; David F. Maynard; John T. Trumble (Journal of Chemical Ecology, 1998)